Removable partial denture design in the general dental practice I. - Márta Radnai; Gyula Marada; Veronika T. Szabó; Tamás Tarjányi; Zoltán Baráth (Hungarian Dental Association, 2021)
Even today, removable partial dentures are often provided by general dental practitioners. The dentists during denture design should take into consideration all the biological, static, material and aesthetic aspects and also the needs and expectations of patients. A questionnaire survey has been conducted among dental technicians to find out how much this is realized in practice. According to the response of 64 dental technicians, who voluntarily filled the anonym questionnaire, a little more than the half (52%) of the dentists send a precise and detailed denture design to the dental technical laboratory. Technicians received information relating the type of the clasps in 47% and a guidance on the shape of major connectors in 28%. Six percent of instructions were provided in drawing, 48% in writing, and 31%. both in writing and drawing. According to the survey in case of problems with the denture, the responsibility was shared between the technician and the dentist, whoever made the planning. 86% of technicians stated that dentists should be fully involved in the design of removable partial dentures. Data from the literature have shown a similar practice, i.e. that dentists in other countries also mainly entrust partial denture design to the dental laboratory, even though this is an incorrect practice.